ANTIBIOTIC PROPHYLAXIS IN PATIENTS UNDERGOING DENTAL IMPLANT PLACEMENT (Ustozlar uchun, 2026)
An analytical review of publications from the PubMed, Cochrane, ResearchGate, and eLibrary databases for the period 2010–2025 was conducted. The results of randomized controlled trials and international guidelines on systemic antimicrobial prophylaxis in dentistry, covering data from more than 1,000 patients, were investigated.